2020
DOI: 10.1007/s35114-020-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

Wie smarte Städte Pandemien bekämpfen können

Abstract: Pandemien stellten Städte schon in der Vergangenheit vor große Herausforderungen. Die wesentlichen Erkenntnisse über den Umgang mit diesen Krankheiten bilden die Grundlage für die Maßnahmen in der heutigen Corona-Pandemie. Eine Kombination mit smarten Technologien verspricht eine wirksame Bekämpfung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A notable collaboration between the private and public sectors is the emergence of "smart governance". Guenduez et al (2020) [18] reported that many historical measures used in previous pandemics are again being relied upon but have been improved through the use of intelligent technologies. For example, artificial intelligence is being used to better understand human behavior, enable rapid and effective contact tracing, demonstrate the effectiveness of interventions, track the evolution of the pandemic, and identify sites that are conducive to spread.…”
Section: Contact Tracing: the Swisscovid Appmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable collaboration between the private and public sectors is the emergence of "smart governance". Guenduez et al (2020) [18] reported that many historical measures used in previous pandemics are again being relied upon but have been improved through the use of intelligent technologies. For example, artificial intelligence is being used to better understand human behavior, enable rapid and effective contact tracing, demonstrate the effectiveness of interventions, track the evolution of the pandemic, and identify sites that are conducive to spread.…”
Section: Contact Tracing: the Swisscovid Appmentioning
confidence: 99%
“…The project, led by Marcel Salathé and Carmela Troncoso at EPFL and ETH, demonstrates the possibilities of reconciling democratic principles with decentralized applications for tracking COVID-19 cases while respecting the constitutional right to privacy. While centralized states use smart technologies to control the population via top-down instructions, democratic systems rely more on decentralized solutions with citizen ownership [18]. The Swiss app COVID-19 is also an example of ideas developed by the public sector in Switzerland and then designed and produced by the private sector, illustrating the success of this fruitful collaboration.…”
Section: Contact Tracing: the Swisscovid Appmentioning
confidence: 99%